The Effect of Emotional Demands, Job Stress and Role Conflict on Burnout Among Healthcare Professionals in Medical Staff in Private Hospitals - Fatimah Malini Lubis; Ita Soegiarto (Dinasti Review, 2026)
The research study investigates how emotional demands and job stress together with role conflict create burnout symptoms among healthcare staff members who work at a private hospital. The researchers used a quantitative approach by distributing questionnaires to 130 participants who were selected through purposive sampling. The study used multiple linear regression to analyze data which required validity tests and reliability tests and the classical assumption tests that included normality and heteroscedasticity and multicollinearity assessments. The research established that emotional demands and job stress together with role conflict create burnout at a statistically significant level because their impacts on burnout showed positive results. The healthcare professionals experienced greater emotional exhaustion because their emotional demands required them to work beyond their mental limits which caused them both mental and physical distress. The three variables together explained more than half of the variations in burnout. The research provides essential information which hospital administrators require to manage psychological and organizational factors that result in burnout while they work to enhance employee health and improve healthcare service quality.